UNDERSTANDING OF MYCOBACTERIUM TUBERCULOSIS EVOLUTION - V. L. Dobin (Туберкулез и болезни лёгких, 2018)
The article presents data from the literature devoted to studying the evolution of M. tuberculosis and the matter of the process which resulted in the modern diversity of tuberculous mycobacteria. Molecular methods with other auxiliary tools helped to change the view on history of M. tuberculosis complex, leading to the development of a new evolutionary scenario.